Ecotourism research: a bibliometric review - Abdurrahman Dinç; Mehmet Bahar; Yunus Topsakal (Tourism & Management Studies)
The paper aims to examine the trends and evolution of ecotourism research in the last 20 years, highlighting co-citations, collaborations, and emerging research themes. A total of 1387 ecotourism-related research from the Web of Science (WoS) database from 1991 to 2021 were analyzed in some bibliometric analyses using CiteSpace V software. The WoS database was scanned using the terms “ecotourism” and “eco-tourism.” While scanning, the “Hospitality, Leisure, Sport, and Tourism” field was selected for filtering, and articles published by September 12, 2021, were accessed. The most frequently studied cluster of topics related to ecotourism includes the creation of local benefits, ecotourism intentions, and community empowerment. The three most frequently used keywords related to ecotourism are “ecotourism,” “tourism,” and “conservation.” The outcome of this research constitutes a unique contribution to the area of ecotourism. The study provides an in-depth bibliometric analysis of publications and identification of important research trends. It also identifies possible avenues for future research in the knowledge domain of ecotourism.